Studi Evaluasi Penggunaan Integrasi Teknologi Pembelajaran di Sekolah Menggunakan Model DEM - Nurul Hasanah; Sitti Mania; Muhammad Nur Akbar Rasyid (South Sulawesi Education Development, 2026)
This study aims to evaluate the implementation of the Smart TV or Interactive Flat Panel Display (IFPD) integration program in the teaching and learning process at junior high schools in Palopo City. Using the Discrepancy Evaluation Model (DEM), the study examines the definition, installation, process, and product stages to identify discrepancies between established program standards and actual implementation in schools. This study employed an evaluative research approach based on the Discrepancy Evaluation Model. Data were collected through interviews, questionnaires, observations, and document analysis involving relevant school stakeholders and program implementation documents. The collected data were analyzed by comparing the expected standards of the program with actual conditions at each evaluation stage. The findings indicate that school readiness at the definition and installation stages was generally adequate, particularly regarding program planning and the availability of technological facilities. However, the instructional implementation remained suboptimal. Teachers had not fully integrated the IFPD into pedagogical practices, and several interactive features were not effectively utilized to support student engagement and learning activities. The Smart TV/IFPD integration program has established adequate technological readiness but has not yet achieved optimal instructional implementation. Targeted and continuous teacher training is required to strengthen digital pedagogical competence and improve the effective use of interactive technology in classroom instruction.